A percepção dos professores sobre o tablet em escolas brasileiras de currículo duplo sob o viés da complexidade - Ragnev, Karem Datti (2018)
This research aims to present the phenomenon the teacher´s perception about the tablet in high school dual-diploma program in Brazilian schools from the perspective of complexity. The phenomenon emerges from the interpretation of the participants’ written records about the use of tablets in their professional and personal contexts. Tablets are a type of mobile device (MD), light weighted, and portable. With a tablet device, it is much easier to access the internet at any time at any place, searching and sharing information at the tip of one´s finger. The learning process is to happen inside and outside the classroom changing and facilitating people´s routine at a tremendous and continuous transformation process. In scholar settings, these changes may raise several assumptions and doubts about its use and potentialities. Thus, this research aims to describe and interpret the phenomenon mentioned above in order to seek for the answer for this enquiry: what is the nature of the phenomenon of the teacher´s perception about the tablet in high school dual-diploma program in Brazilian schools from the perspective of complexity? The theoretical foundation of this research is the theory of complexity by Morin (2005, 2010, 2011, 2013, 2015, and 2016). Furthermore, (a) some other studies concerning the changes in the student´s learning profile and the teacher´s profile in this new technological era by Moran (1995); (b) about the relationships between the new digital cultural scenarios with the ubiquitous learning process by SANTAELLA (2010), JENKINS (2006), and KENSKI (2012) and by LEVY (2000); (c) about teacher education and self-hetero-eco technologic formation process grounded on complexity principles by FREIRE and LEFFA (2013), MORAES (2008, 2014) are taken into account. Aiming to investigate and interpret the phenomenon, the methodological choice is the Complex Hermeneutic-Phenomenological Approach (FREIRE, 2017). In this approach, it is possible to describe and interpret the phenomena of human experience based on complexity. The research participants were 3 teachers from two high school dual-diploma program in Brazilian schools, where tablet has been used. A profile survey and written reports have been used as instruments for gathering texts. In the interpretation of the texts originated from the participants, it was possible to identify the themes that compose the phenomenon under this study: application, usability, receptivity, resistance, navigability, planning e sustainability. At the end of this lived experience, it was possible to understand the importance of adopting a systemic and complex perspective when tackling with mobile technology and its possible influences in scholar settings, aiming to establish connections with world outside the school in order to empower learners to act more critically and ethically in the real world